Leadership and professional development in schools : how to promote techniques for effective professional learning - Burnham, John W.; O'Sullivan, Fergus (London : Prentice hall, 1998)
This book suggest practical strategies for professional development within your school. Using case studies and the experience of leading practitioners, Leadership and Professional Development in Schools helps you to
includes references and index.
Keywords: Teachers -- In-service training; Organisatieontwikkeling; Management